The effect of steel wire mesh on mechanical properties of ADOBE - Yahya Al-Tawil, Yahya Mohsen (2017)
The aim of this research is to investigate basic properties of soil mixture using wire mesh as support strength. The soil mixture consists of sand, soil, clay, silt and Kenaf. Adobe buildings are encountered in almost every region of the world and constitute a significant feature of the international cultural heritage. However, the behaviour of adobe materials and earth has not yet been adequately investigated. Ecologic building materials such as adobe bricks have become of greater economic importance in recent years. Adobe is a form of natural architecture built with environment friendly materials which provide indoor protection from outside temperature conditions. It is important to consider the strength of adobe brick. This study was conducted to determine the effect of the strength among the sample with wire mesh and without wire mesh on adobe brick. As the experimental program was planned, consisting tests such as compressive strength and flexural strength, were conducted to investigate the strength of adobe bricks. The result showed that the use of wire mesh increases the compressive strength 40% to 50% respectively. In addition, that, wire mesh increases the compressive strength of adobe bricks. For this measure of study the impact for using wire mesh on compressive strength test is noticeable. However, adobe is good in taking flexural stresses. The samples treated with wire mesh exhibits highest compressive and flexural strength test. The average of the cubes and beams sample have shown usage of wire mesh has increased the strength of the samples. Thus, the impact of wire mesh on flexural strength and compressive strength of adobe is noticeable.